Ship Sanitation and Sanitary Behavior of the Crew Influences to the Presence of Rats on Cargo Ship in the Port of Tanjung Perak Surabaya - Sofiyan Sofiyan; Soedjajadi Keman (Universitas Airlangga, 2017)
Sanitary inspection intended to eliminate environmental risk factors in the ships to break the chain disease transmission in order to maintain and enhance the health status. Based on data from 2015 the Port Health Office class I Surabaya, during the ships inspection there are found 23 rats from 2734 ships. The existence of the rats on the cargo ship is very harmful, which can caused disease and damaged food material in cargo ship. The tendency of rats existence on board as media transmission of the disease, is the reason for researchers to identify the level of sanitation review and behavior of crew that affecting the existence of rats on cargo ship in the Port of Tanjung Perak Surabaya. That research aimed to analyze the level of sanitation and behavior of crew that affects the existence of rats. This study was an observational study with cross sectional study design, sampling for ship sanitation in research using accidental sampling, behavior of crew using the proportional random sampling method. The research variables are behavior of crew and ship sanitation. The primary data were collected by observation, indepth interviews, and questionnaires. Secondary data collected from the Port Health Office Class I Surabaya. Statistical test with multiple regression showed that behavior of crew significant effect on the existence of rat in cargo ship. The results using ship sanitation level variables sig. 0.043 means that the behavior of crew variable significant effect on the presence of rats on a cargo ship, while for the ship sanitation variables sig. 0.0002, means that the variable ship sanitation very significantly affected on the presence of rats on a cargo ship. The conclusion of this study be found influences of the ship sanitation and behavior of crew against the presence of rats in cargo ship, so it needs to be disseminated to the crew of cargo ship in order to increase knowledge about ship sanitation, and the health effects of the presence of rats on a cargo ship.